Investigation of the slow relaxation of the magnetization dynamics in homoleptic ene-diamido organodysprosium(iii) complexes with K+/arene interactions. Issue 25 (11th June 2020) - Long, Jérôme; Tolpygin, Aleksei O.; Cherkasov, Anton V.; Lyssenko, Konstantin A.; Guari, Yannick; Larionova, Joulia; Trifonov, Alexander A.
Abstract : Two new Dy 3+ homoleptic ate -complexes based on different ene-diamido ligands [K(THF)2 ][Dy(DAD 2R )2 ] (DAD = [2, 6-iPr2 C6 H3 N–CRCR–NC6 H3 iPr2 -2, 6], R = H, Me) show K + /arene interactions and single-molecule magnet behavior. Abstract : We report the synthesis, structure and magnetic investigations of two new Dy 3+ homoleptic ate -complexes based on different ene-diamido ligands [K(THF)2 ][Dy(DAD 2R )2 ] (R = H (1 ), Me (2 ) DAD 2R = [2, 6-iPr2 C6 H3 N–CRCR–NC6 H3 iPr2 -2, 6] showing K + /arene interactions. Magnetic investigations reval that both compounds exhibit a zero-field single-molecule magnetic relaxation mainly governed by a Raman process.